2007
DOI: 10.1074/jbc.m701590200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Substrate-free Human Insulin-degrading Enzyme (IDE) and Biophysical Analysis of ATP-induced Conformational Switch of IDE

Abstract: Insulin-degrading enzyme (IDE) is a zinc metalloprotease that hydrolyzes amyloid-␤ (A␤) and insulin, which are peptides associated with Alzheimer disease (AD) and diabetes, respectively. Our previous structural analysis of substratebound human 113-kDa IDE reveals that the N-and C-terminal domains of IDE, IDE-N and IDE-C, make substantial contact to form an enclosed catalytic chamber to entrap its substrates. Furthermore, IDE undergoes a switch between the closed and open conformations for catalysis. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
208
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(219 citation statements)
references
References 51 publications
11
208
0
Order By: Relevance
“…However, it has also been reported that ATP can increase degradation of small peptides by IDE, while having little effect on insulin metabolism [16,17]. Whatever the effect on insulin degradation, ATP does induce a conformational change in IDE [16]. We have shown that IDE activity is inhibited non-competitively by select free fatty acids and their coenzyme A thioesters [18].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, it has also been reported that ATP can increase degradation of small peptides by IDE, while having little effect on insulin metabolism [16,17]. Whatever the effect on insulin degradation, ATP does induce a conformational change in IDE [16]. We have shown that IDE activity is inhibited non-competitively by select free fatty acids and their coenzyme A thioesters [18].…”
Section: Introductionmentioning
confidence: 57%
“…Camberos et al showed ATP inhibited insulin degradation [15]. However, it has also been reported that ATP can increase degradation of small peptides by IDE, while having little effect on insulin metabolism [16,17]. Whatever the effect on insulin degradation, ATP does induce a conformational change in IDE [16].…”
Section: Introductionmentioning
confidence: 99%
“…The time course of insulin digestion by the dissociating the IDE⅐NTE-2 complex can be obtained by substituting K cat (app) from Equation 7 for the K cat in Equation 5. Fitting of the data were performed using Mathematica software (Wolfram Research).…”
Section: Methodsmentioning
confidence: 99%
“…Addi-* All authors were employees and shareholders of Eli Lilly and Company at the time this work was completed. tionally, the enzyme is known to be activated by ATP, which destabilizes the closed form of the enzyme (5). Both Türkay and co-workers (17) and Leissring and co-workers (18) have reported the identification of additional unique small molecules that show the ability to activate the enzyme with substrate specificity.…”
mentioning
confidence: 99%
See 1 more Smart Citation